Factors Influencing the Collection of Non Timber Forest Products by Forest Dwellers in Nagaland, India - Das, Sanjoy; Longkumer, Narokumla; Ozukum, Limasunep; Ngullie, Thungdemo (Indian Journal of Agroforestry, 2022)
Present study was conducted to identify the factors influencing the collection of Non Timber Forest Products by forest dwellers in Nagaland. It was conducted in Mokokchung District of Nagaland. Out of 6 R.D.Blocks in the district, two blocks namely, Changtongya block and Ongpangkong N block were chosen purposively for the study. Proportionately 25% villages were selected from both the blocks. Finally 100 respondents were randomly selected from 10 villages. Collected data were processed and analysed using simple analytical tools. Regression analysis was used in order to determine the factors influencing NTFPs income of sample households. Garrett ranking technique was also used to identify the factors influencing collection of NTFPs by sample households. Â It was found that majority of forest dwellers in Nagaland went for collection of NTFPs mainly because of traditional norms followed by Naga society. At the same time people went for collection of NTFPs because NTFPs are good source of income as well as good source of food. Dependency ratio and employment from NTFPs were found significant factors and positively related with income from NTFPs. As the number of dependents increased, they went for NTFPs collection since they found it convenient compared to other activities. For every one percent increased in Dependency, income from NTFPs increased by Rs.279.33 and for every one man day increase in employment from NTFPs, NTFPs income increased by Rs. 554.08.